Preaching as master's discourse. A Foucauldian interpretation of Lutheran pastoral power. (August 2019) - Tilli, Jouni
Michel Foucault acknowledged that the Reformation was a pastoral battle and a reorganization of pastoral power. He did not, however, analyze Protestantism much further. This article broadens the scope of critical research on Protestantism, focusing on Lutheranism. Preaching is a fruitful way to overcome overemphasis on confession. In this endeavor I apply Foucault's concept of "master's discourse." I argue that while, in Lutheranism, conversion through comprehensive soul-searching is an individual matter, at the same time it relies on technologies aimed at a collective audience, such as preaching. Since preaching is divine speech, the Lutheran priest wields enormous spiritual power: the preacher is the truth-teller and the subject is required to listen to and internalize the proclaimed truth, instead of confessing their sins.